In defense of juveniles sentenced to life: legal representation and juvenile criminal justice - Kokkalera, Stuti (Routledge contemporary issues in criminal justice and procedure, 2022)
The meaning of a meaningful opportunity -- The evolving right to legal representation -- What about effective legal representation for juvenile lifers? -- Study setting, data, and methods -- Contextualizing the role of counsel in parole -- Conclusion : in defense of juveniles sentenced to life.